Bronchoscopic View of an Intracavitary Aspergilloma (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Aspergilloma, also known as mycetoma or fungal ball, is caused by pulmonary involvement of Aspergillus species in a pre-existing lung cavity as evidenced by air crescent sign in computed tomography scan of chest. Direct visualization of aspergilloma in cavity is a rare bronchoscopic finding.J Bangladesh Coll Phys Surg 2025; 43: 186-187